A Case of Persistent Hiccup after Laparoscopic Cholecystectomy. (4th April 2013) - Grifoni, Elisa; Marchiani, Costanza; Fabbri, Alessia; Ciuti, Gabriele; Pavellini, Andrea; Mancuso, Francesco; Viligiardi, Riccardo; Moggi Pignone, Alberto
Abstract : A 79-year-old man, with history of recent laparoscopic cholecystectomy, came to our attention for persistent hiccup, dysphonia, and dysphagia. Noninvasive imaging studies showed a nodular lesion in the right hepatic lobe with transdiaphragmatic infiltration and increased tracer uptake on positron emission tomography. Suspecting a malignant lesion and given the difficulty of performing a percutaneous transthoracic biopsy, the patient underwent surgery. Histological analysis of surgical specimen showed biliary gallstones surrounded by exudative inflammation, resulting from gallbladder rupture and gallstones spillage as a complication of the previous surgical intervention. This case highlights the importance of considering such rare complication after laparoscopic cholecystectomy.